DEVELOPMENTS AND USING OF COMPLEX PREPARATIONS FOR REFINEMENT AND MODIFICATION OF ALUMINIUM ALLOYS - S. P. Korolyov; A. M. Galushko; V. M. Mihajlovskij (Литьë и металлургия)
Different reactions of interaction of such modifiers as sodium, strontium, sulfur, phosphorus and rare-earth elements with components, impurity of aluminum alloys and between each other, are investigated.